2014
DOI: 10.17843/rpmesp.2014.314.133
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la política para el control de la tuberculosis en Colombia

Abstract: Se pretende analizar la política para el control de la tuberculosis en Colombia entre 1975 y 2010. Durante los años 80 se observó un esfuerzo en la gestión de los programas de control que se reflejó en la reducción de la incidencia y en mortalidad. A partir de 1993, cuando se desmontó el Sistema Nacional de Salud y se privatizó la gestión de los recursos, los indicadores de desempeño del programa de control mostraron un deterioro importante. A partir de 2009 se observa un esfuerzo por precisar y fortalecer la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
3
Order By: Relevance
“…Although TB mortality decreased for both sexes during the study period, the joinpoint regression showed a statistically significant decrease of the ASMR between 1999 and 2012/2011 among men and women, respectively, with a subsequent stagnation for both sexes. The first period of reduction may reflect the efforts of national programs to improve the availability of effective chemotherapy and diagnosis 42 . The explanation for this does not seem to be related to the strategies adopted to achieve the Millennium Development Goals (MDGs).…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TB mortality decreased for both sexes during the study period, the joinpoint regression showed a statistically significant decrease of the ASMR between 1999 and 2012/2011 among men and women, respectively, with a subsequent stagnation for both sexes. The first period of reduction may reflect the efforts of national programs to improve the availability of effective chemotherapy and diagnosis 42 . The explanation for this does not seem to be related to the strategies adopted to achieve the Millennium Development Goals (MDGs).…”
Section: Sexmentioning
confidence: 99%
“…The explanation for this does not seem to be related to the strategies adopted to achieve the Millennium Development Goals (MDGs). On the other hand, these inequalities may also be mediated by the structural characteristics of the health system in Colombia, which underwent significant changes after the implementation of Law 100/1993, a reform that moved from a National Health System (financed by taxes and revenues and controlled by the Colombian Ministry of Health) to a privatized resource managed by insurers 42 ; that increased the coverage of the affiliation to the General System of Social Security in Health (SGSSS), but segmented the quality of the services according to income 43 .…”
Section: Sexmentioning
confidence: 99%
“…Algunos estudios realizados en Colombia han analizado cómo el funcionamiento del SGSSS y los procesos de descentralización en salud a nivel local han afectado la adecuada respuesta institucional a algunos eventos de interés en salud pública (22–25). Con respecto a la inmunización, una investigación analizó el PAI en tres municipios colombianos en relación con el SGSSS y encontró que estos no estaban preparados para los profundos cambios institucionales que implicó el nuevo sistema de salud desde 1994.…”
Section: Discussionunclassified
“…La promoción de la salud y la prevención de la enfermedad se convirtieron en una expresión vulgar denominada "P y P", desconociendo los avances anteriores en salud y separándose el Gobierno de los pactos, las declaraciones y los lineamientos de los organismos internacionales en salud (Organización Panamericana de la Salud -ops-, Organización Mundial de la Salud Universidad de Antioquia -oms-), compromisos adquiridos por el Gobierno de Colombia, pero no asumidos [23,24]. Las acciones de salud pública que promueven, preservan y protegen la salud, con alto impacto colectivo y con altas externalidades, no fueron privilegiadas por la ideología neoliberal individualista y por la baja rentabilidad económica que representan, lo que ha incrementado las enfermedades transmisibles controladas en el pasado (cólera, dengue hemorrágico y las enfermedades inmunoprevenibles) [19,[25][26][27][28][29].…”
Section: Crisis Del Sistema General De Seguridad Social En Saludunclassified